Student Obstacles in Choosing Extracurricular Activities at SMAN 3 Kota Solok - Jefri Indra Pratama; Vevi Sunarti (Universitas Negeri Padang, 2023)
This research was motivated by the low interest of students in choosing scout extracurricular activities at SMAN 3 Solok. It is suspected that there are factors that cause the lack of student interest including the lack of support from school leaders, lack of motivation from the coaches, inadequate existing facilities, thus making students less interested in choosing scout extracurricular activities. The aims of this study are: (1) to describe the constraints in the aspect of school leadership support for scout extracurricular activities; (2) Describe the obstacles in the aspect of the role of the coach to the program in overcoming the obstacles of students to choose scout extracurricular activities; (3) Describe the obstacles in the aspect of providing facilities provided by the school to scout extracurricular activities; (4) Describe the obstacles in the aspect of student interest in choosing scout extracurricular activities. This type of research is quantitative descriptive with a population of 70 people, with a sampling technique of 60% of the population as many as 35 people. This study shows the results, namely: (1) school leadership support for scout extracurricular is less supportive; (2) students' obstacles in choosing extracurricular are not good; (3) facilities and infrastructure as well as the role of coaches in extracurricular activities at SMA 3 Kota Solok do not become obstacles for students in choosing extracurricular activities.